Communitas - Turner, E. author. aut Link
XIV, 258 p.
Keywords: Communitas is inspired fellowship; a group's pleasure in sharing common experiences; being 'in the zone' - as in music, sport, and work; the sense felt by a group when their life together takes on full meaning. The experience of communitas, almost beyond strict definition and with almost endless variations, often appears unexpectedly.